The Effect of Atenolol on Thyroid Hormons in Subclinical Hyperthyroidism: Effect of atenolol on thyroid hormons - Abbasi Nazari, Mohammad; Mohammadpoor, Amir Hoshang; Behjati Ardakani, Javad; Rouini, Mohammad Reza; Gholami, Kheirollah (Iranian Journal of Pharmaceutical Sciences, 2005)
This Study was performed to evaluate the effect of atenolol on the serum concentration of TT4 and TT3 in subclinical hyperthyroid patients. Due to the i n s u fficient information about the effect of atenolol on serum level of these hormones, the aim of this research was to shade some light on the subject. Fifteen subclinical hyperthyroid patients entered this study. Each patient received 100 mg/day atenolol. The serum concentration of atenolol, TT4 and TT3 were measured before starting the administration of the drug and on the first, third and seventh day after atenolol administration was started. The serum concentrations of TT4, but not TT3, on the third and seventh day were increased significantly in comparison to the baseline TT4. There was no correlation between plasma atenolol concentration and changes in TT4 and TT3.